First molecular identification of Suillia gigantea (Meigen, 1830) (Diptera: Heleomyzidae) - Rosa-Gruszecka, Aleksandra; Woźnica, Andrzej Józef; Tereba, Anna; Szabłowski, Przemysław; Hilszczańska, Dorota (Zootaxa, 2023)
In 2017, the presence of the fly Suillia gigantea (Meigen, 1830) was noted in Poland, after many years of research related to the ecology of insects associated with the fruiting bodies of hypogeous fungi. Finally, in 2020, after further studies, the distribution of the truffle fly in Poland was confirmed. Six adults were reared from larvae inhabiting the fruiting bodies of Burgundy truffle (Tuber aestivum Vittad. (1831)). The fungi were harvested in southern Poland. Morphological and genetic analyses of the insect specimens were performed. For the first time, the DNA sequence of this fly species was isolated. This is the first record of S. gigantea in Poland, although it has already been reported from neighbouring countries. The development of S. gigantea, also known as the truffle fly, is associated with hypogeous fungi, mainly belonging to the genus Tuber P. Micheli ex F.H. Wigg. (1780). The diptera larvae develop inside the fruiting bodies. This type of damage causes great losses in truffle production. Containment of these losses is of great interest to the truffle industry. Knowledge of truffle-inhabiting insects is crucial for the development of effective methods to protect truffle crops in Europe.